Adverse events following immunization during COVID-19 mass vaccination campaigns in the Democratic Republic of Congo: Findings from active safety surveillance - Kizito Kayumba; Alemayehu Duga; Mosoka Papa Fallah; Claire Tshidibi; Nicky Lubaki; Barnabas Coulibaly; Benjamin Djoudalbaye; Efire Nora Sylvana; Senga Lucy Sembuche; Tedi Tilahun; Murtala Jibril; Carlos Kilowe; et al. (PLoS ONE, 2026)
Introduction Post-marketing safety surveillance is essential for ensuring vaccine safety and maintaining public trust, particularly in African settings where evidence on the safety of COVID–19 vaccines remains limited. This study aimed to determine the overall incidence and types of AEFIs, as well as the factors associated with their occurrence, during COVI-19 mass vaccination campaigns in Democratic Republic of Congo. Methods From December 1–29, 2023, a prospective safety surveillance study was conducted in Kinshasa Province. Participants were surveyed through phone calls from day 1–28 following COVID-19 vaccine administration. AEFI incidence rates were calculated by type of vaccine, sex, number of dose and age group. Factors associated with AEFIs were identified using multivariable logistic regression models, expressed by adjusted odds ratio and its 95% confidence interval. Results The study included 4766 participants. Their median [IQR] age was 36 [27−48] years and 2503 (53%) were males, 94.63% received the J&J vaccine while 256 (5.37%) received the BNT162b2 vaccine. Incidence of AEFIs was 23.75% (95%CI: 22.54%−24.99%). AEFIs mostly reported were fever (9.61%, 95%CI: 8.88%−10.48%), injection site pain (9.00%, 95%CI: 8.20%−9.85%), headache (4.11%, 95%CI: 3.57%−4.72%), stiffness (1.51%, 95%CI: 1.18%−1.89%) and myalgia (1.15%, 95%CI: 0.87%−1.49%). The incidence of AEFIs was higher for the BNT162b2 vaccine at 34.48% (95% CI: 28.57%−40.54%) vs. 23.15% (95% CI: 21.92%−24.41%) for the J&J vaccine. Compared to participants aged 18−59 years, those under 18 years old were associated with decreased odds of reporting any AEFI (aOR= 0.26, 95%CI: 0.13–0.88) and injection site pain (aOR=0.18, 95%CI: 0.05–0.75). Those aged 60 years and older were associated with decreased odds of reporting any AEFI (aOR= 0.78, 95%CI: 0.62–0.99) and fever (aOR=0. 63, 95%CI: 0.43–0.92). Conclusions Approximately one-quarter of participants reported AEFI. The observed association with vaccine type and age underscores the need for systematic vaccine safety monitoring in the population. This is critical for guiding future vaccination strategies tailored to individuals who may be more susceptible to AEFIs.